Bacterial community of brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) revealed by high throughput amplicon sequencing - Tyagi, S; Srinivasa, N; Singh, R N; Arya, V (Plant Science Today, 2025)
The bacterial symbionts of brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), a key sucking insect pest of rice in India and Asia, have been known to play many important physiological functions. Reports of yeast-like symbionts of N. lugens are widely known, but little is known about the bacterial microbes. In this study, the bacterial community structure and diversity were examined in N. Lugens collected from four major rice-growing regions of India utilizing culture-independent high throughput sequencing. The Mi seq technology identified a total of 1277 operational taxonomic units (OTUs) representing 4 phyla mainly (Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes) by analyzing 16S rDNA gene libraries. The major microbial groups were similar in the four samples, but their distribution patterns were different, especially in Raichur. While the top three bacterial genera linked to Imphal, Pantnagar, and Raichur were Methylobacterium, Sphingomonas, and Acinetobacter; Wolbachia accounted for 87.46% of the total genera found in Raipur. The identified dominant microbial groups have been known for their crucial role in insect’s life cycle. Diversity analysis tests revealed Raichur has the highest species diversity as determined by the high Shannon and Simpson index. According to ACE and Chao1 diversity estimates, Pantnagar has the highest species richness. Understanding the bacterial communities and studying their functional roles will help in formulating biological control strategies specific to this sucking pest.